Pengurusan Izin Olah Gerak Kapal MT. Ship Trinity Dari Area Dock ke Area Labuh pada PT. Multi Jaya Samudera Belawan - Richa Anjelina; Netty Kesuma; Fadiyah Hani Sabila (International Forum of Researchers and Lecturers, 2023)
This study focuses on the process of managing the Ship Movement Permit for MT.SHIP TRINITY during its transfer from the dock area to the anchorage area at PT. Multi Jaya Samudera Belawan. As an intermediary company, PT. Multi Jaya Samudera Belawan is committed to finding cargo ships with high-quality standards to provide the best service to customers, while prioritizing safety and maritime environmental protection. In its capacity as a shipping company, PT. Multi Jaya Samudera handles ship movement permit management through several stages, including administrative compliance, permit application, and ship document completion. This process needs to be carried out quickly and accurately to avoid delays, which requires good coordination with various related agencies at the port. The role of PT. Multi Jaya Samudera Belawan is crucial in supporting ship service activities in the shipping industry. To optimize port operations, appropriate management policies are needed to improve the overall effectiveness and efficiency of port performance.